Essential anatomy of the cranial cavity and brain - Keenan, Iain D. (Henry Stewart Talks, 2025)
Cranial cavity and brain embryological origins, Bones of neurocranium, Meninges, Internal surfaces and cranial nerve foramina, Key structures of the brain, Forebrain, midbrain and hindbrain, Blood supply and venous drainage